Numerical investigation on the transition of fluid flow characteristics through a rotating curved duct - Hasan, Mohammad Sanjeed; Islam, Md. Sirajul; Badsha, Md. Faisal; Mondal, Rabindra Nath; Lorenzini, Giulio (Zielona Góra: Uniwersytet Zielonogórski)
Time-dependent flow investigation through rotating curved ducts is utilized immensely in rotating machinery and metal industry. In the ongoing exploration, time-dependent solutions with flow transition through a rotating curved square duct of curvature ratio 0.009 have been performed.
Keywords: rotating curved duct; Taylor number; flow transition; secondary flow; heat transfer